A Case-Control Study on the Impact of Ventilator-Associated Tracheobronchitis in the PICU*. Issue 6 (July 2015) - Wheeler, Derek S.; Whitt, John D.; Lake, Michael; Butcher, John; Schulte, Marion; Stalets, Erika
<x xml:space="preserve">Abstract</x> Objectives: Hospital-acquired infections increase morbidity, mortality, and charges in the PICU. We implemented a quality improvement bundle directed at ventilator-associated pneumonia in our PICU in 2005. We observed an increase in ventilator-associated tracheobronchitis coincident with the near-elimination of ventilator-associated pneumonia. The impact of ventilator-associated tracheobronchitis on critically ill children has not been previously described. Accordingly, we hypothesized that ventilator-associated tracheobronchitisis associated with increased length of stay, mortality, and hospital charge. Design: Retrospective case-control study. Patients: Critically ill children admitted to a quaternary PICU at a free-standing academic children's hospital in the United States. Interventions: None. Measurements and Main Results: We conducted a retrospective case control study, with institutional review board approval, of 77 consecutive cases of ventilator-associated tracheobronchitis admitted to our PICU from 2004-2010. We matched each case with a control based on the following criteria (in rank order): age range (< 30 d, 30 d to 24 mo, 24 mo to 12 yr, > 12 yr), admission Pediatric Risk of Mortality III score ± 10, number of ventilator days of control group (> 75% of days until development of ventilator-associated tracheobronchitis), primary diagnosis, underlying organ system dysfunction, surgical procedure, and gender. The primary outcome measured was PICU length of stay. Secondary outcomes included ventilator days, hospital length of stay, mortality, and PICU and hospital charges. Data was analyzed using chi square analysis and p less than 0.05 was considered significant. We successfully matched 45 of 77 ventilator-associated tracheobronchitis patients with controls. There were no significant differences in age, gender, diagnosis, or Pediatric Risk of Mortality III score between groups. Ventilator-associated tracheobronchitis patients had a longer PICU length of stay (median, 21.5 d, interquartile range, 24 d) compared to controls (median, 18 d; interquartile range, 17 d), although not statistically significant (p = 0.13). Ventilator days were also longer in the ventilator-associated tracheobronchitis patients (median, 17 d; IQR, 22 d) versus control (median, 10.5 d; interquartile range, 13 d) (p = 0.01). There was no significant difference in total hospital length of stay (54 d vs 36 d; p = 0.69). PICU mortality was higher in the ventilator-associated tracheobronchitis group (15% vs 5%; p = 0.14), although not statistically significant. There was an increase in both median PICU charges ($197, 393 vs $172, 344; p < 0.05) and hospital charges ($421, 576 vs $350, 649; p < 0.05) for ventilator-associated tracheobronchitis patients compared with controls. Conclusions: Ventilator-associated tracheobronchitis is a clinically significant hospital-acquired infection in the PICU and is associated with longer duration of mechanical ventilation and healthcare costs, possibly through causing a longer PICU length of stay. Quality improvement efforts should be directed at reducing the incidence of ventilator-associated tracheobronchitis in the PICU.